Antifibrinolytic Therapy for Cardiac Surgery: An Update. (July 2015) - Koster, Andreas; Faraoni, David; Levy, Jerrold H.
Abstract : Antifibrinolytic therapy reduces bleeding and chest tube drainage output in cardiac surgical patients but is associated with potential side effects. Two phase-II studies with new compounds were terminated prematurely. There is increasing evidence of adverse side effects with tranexamic acid.